2012
DOI: 10.5897/jmpr11.1103
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Brassica napus as a medicinal food plant

Abstract: Brassica napus L. (B. napus L) (Cruciferae), is one of the cultivated medicinal food plants in Middle Asia, North Africa and West Europe. In Iranian traditional medicine, the root parts of this plant were used for the therapeutic properties as diuretic, anti-scurvy, anti-inflammatory of bladder and anti-goat. The usage of rapeseed oil as a food product as well as in the production of non-nutrition products such as greases, lubricant oils and especially bio-fuel may cause the increasing in rapeseed production i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 22 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…This could be explained by the presence of steroids in pollen, which could affect cancer cells' viability, notably in the prostate [258][259][260]. Apart from the leaves, rapeseed roots are also beneficial because of their various diuretic, anti-gout, anti-inflammatory, and anti-scurvy qualities [261]. Some recent studies have demonstrated that rapeseed has a good performance against Alzheimer's [262] and prostate disease [263].…”
Section: Vegetable Food Tea and Homeopathymentioning
confidence: 99%
“…This could be explained by the presence of steroids in pollen, which could affect cancer cells' viability, notably in the prostate [258][259][260]. Apart from the leaves, rapeseed roots are also beneficial because of their various diuretic, anti-gout, anti-inflammatory, and anti-scurvy qualities [261]. Some recent studies have demonstrated that rapeseed has a good performance against Alzheimer's [262] and prostate disease [263].…”
Section: Vegetable Food Tea and Homeopathymentioning
confidence: 99%
“…Although some secondary plant metabolites are thought to have disease-protecting properties in vivo, they are non-essential nutrients for humans. Phytochemicals from plants were shown to exhibit different biological activities, such as anti-inflammatory [41,42,43,44], anti-microbial [45,46], anti-carcinogenic [46,47] and anti-diabetic properties [48,49]. Some of these are due to the regulation of several cellular molecular pathways [50].…”
Section: Neurodegenerative Diseasementioning
confidence: 99%
“…Rapeseed ( Brassica napus L., AACC, 2n = 38) is an important oilseed crop worldwide, serving as a source of edible vegetable oil and feed meal ( Saeidnia and Gohari, 2012 ; Carruthers et al., 2017 ; Kaur et al., 2020 ). Increasing seed oil content is an important breeding objective in rapeseed.…”
Section: Introductionmentioning
confidence: 99%